PENGEMBANGAN LKPD BERBASIS STRATEGI MOTIVASI ARCSMATERI SISTEM IMUNITAS PADA KELAS XI MIAMAMADANIALAUDDIN PAOPAO - Fitriani A; Muhammad Khalifah Mustami; Hamansah Hamansah (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2019)
The purpose of this study was to develop learning devices namely LKPD based on ARCS motivation strategies (Attention, Relevance, Confidence, Satisfaction) and to determine the level of validity, practicality and effectiveness of the developed LKPD. This research is a development research (Research and Development) to produce products in the form of LKPD based on ARCS motivational strategies for immune system material. This research and development refers to the 4-D development model, which includes four stages, namely defining, designing, developing, and disseminating. The research subjects were students of class XI MIA MA Madani Alauddin Paopao 2018/2019 academic year totaling 35 people. The research instrument was a validation sheet to obtain product validity data, questionnaire responses for students to obtain product practicality data, and test items to obtain data on the effectiveness of the products developed. Based on the results of the expert validator's assessment, the validity level of the LKPD-based strategy for the motivation of the ARCS immunity system material is in a very valid category with an average value of 3.54 (3.5 ≤ X ≤ 4.0). Based on the results of the assessment of students' responses the practicality level of the LKPD is in the practical category with an average total score of 3.32 (2.5 ≤ Xi <3.5). Based on the results of student learning tests the level of effectiveness of LKPD is in the high category, namely 82.86% with the number of students completing in the learning process is 29 people, while the incomplete ones are 6 people. This indicates that the LKPD was developed effectively for use in immunity system material.